Translocating deadwood in ecological compensation benefits saproxylic beetles, but effects are dependent on substrate density - Olov Tranberg; Therese Löfroth; Anne-Maarit Hekkala; Mari Jönsson; Timothy Work; Heloise Gibb; Lukas Holmström; Jörgen Sjögren; Joakim Hjältén (Journal of Environmental Management, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Reintroduction of threatened digging mammals influences soil microbial communities differently along a rainfall gradient - Orsi Decker; Eleonora Egidi; Anna J.M. Hopkins; Melissa Danks; Heloise Gibb (Pedobiologia, 2023)

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

Experimental evidence for ecological cascades following threatened mammal reintroduction - Heloise Gibb; Colin J. Silvey; Chloe Robinson; Felicity A. L'Hotellier; David J. Eldridge (Ecology, 2021)
Species extinction has reached unprecedented rates globally, and can cause unexpected ecological cascades. Since Europeans arrived in Australia, many endemic mammals have declined or become extinct, but their ecological roles and outcomes of their reintroduction for ecosystems are poorly understood. Using surveys and novel long‐term exclusion and disturbance experiments, we tested how digging mammal reintroduction affects predatory invertebrates. Mammal exclusion tended to decrease bare ground. Although scorpion burrow abundance increased with bare ground, mammals also had direct negative effects on scorpions. Increased disturbance alone decreased scorpion abundance, but other mechanisms, such as predation, also contributed to the mammal effect. Despite negative associations between scorpions and spiders, both groups increased and spider composition changed following mammal exclusion. Our long‐term research showed that threatened digging mammals drive ecosystem cascades, affecting biota through a variety of pathways. Reintroductions of locally extinct digging mammals can restore ecosystems, but ecosystem cascades may lead to unexpected restructuring.

Digging mammal reintroductions reduce termite biomass and alter assemblage composition along an aridity gradient - Nicole V. Coggan; Heloise Gibb (Oecologia, 2019)

Thermoregulatory traits combine with range shifts to alter the future of montane ant assemblages - Tom R. Bishop; Catherine L. Parr; Heloise Gibb; Berndt J. van Rensburg; Brigitte Braschler; Steven L. Chown; Stefan H. Foord; Kévin Lamy; Thinandavha C. Munyai; Iona Okey; Pfarelo G. Tshivhandekano; Victoria Werenkraut; et al. (Global Change Biology, 2019)
Predicting and understanding the biological response to future climate change is a pressing challenge for humanity. In the 21st century, many species will move into higher latitudes and higher elevations as the climate warms. In addition, the relative abundances of species within local assemblages are likely to change. Both effects have implications for how ecosystems function. Few biodiversity forecasts, however, take account of both shifting ranges and changing abundances. We provide a novel analysis predicting the potential changes to assemblage‐level relative abundances in the 21st century. We use an established relationship linking ant abundance and their colour and size traits to temperature and UV‐B to predict future abundance changes. We also predict future temperature driven range shifts and use these to alter the available species pool for our trait‐mediated abundance predictions. We do this across three continents under a low greenhouse gas emissions scenario (RCP2.6) and a business‐as‐usual scenario (RCP8.5). Under RCP2.6, predicted changes to ant assemblages by 2100 are moderate. On average, species richness will increase by 26%, while species composition and relative abundance structure will be 26% and 30% different, respectively, compared with modern assemblages. Under RCP8.5, however, highland assemblages face almost a tripling of species richness and compositional and relative abundance changes of 66% and 77%. Critically, we predict that future assemblages could be reorganized in terms of which species are common and which are rare: future highland assemblages will not simply comprise upslope shifts of modern lowland assemblages. These forecasts reveal the potential for radical change to montane ant assemblages by the end of the 21st century if temperature increases continue. Our results highlight the importance of incorporating trait–environment relationships into future biodiversity predictions. Looking forward, the major challenge is to understand how ecosystem processes will respond to compositional and relative abundance changes.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Ant assemblages have darker and larger members in cold environments - Tom R. Bishop; Mark P. Robertson; Heloise Gibb; Berndt J. van Rensburg; Brigitte Braschler; Steven L. Chown; Stefan H. Foord; Thinandavha C. Munyai; Iona Okey; Pfarelo G. Tshivhandekano; Victoria Werenkraut; Catherine L. Parr (Global Ecology and Biogeography, 2016)
Aim In ectotherms, the colour of an individual's cuticle may have important thermoregulatory and protective consequences. In cool environments, ectotherms should be darker, to maximize heat gain, and larger, to minimize heat loss. Dark colours should also predominate under high UV‐B conditions because melanin offers protection. We test these predictions in ants (Hymenoptera: Formicidae) across space and through time based on a new, spatially and temporally explicit, global‐scale combination of assemblage‐level and environmental data. Location Africa, Australia and South America. Methods We sampled ant assemblages ( n = 274) along 14 elevational transects on three continents. Individual assemblages ranged from 250 to 3000 m a.s.l. (minimum to maximum range in summer temperature of 0.5–35 °C). We used mixed‐effects models to explain variation in assemblage cuticle lightness. Explanatory variables were average assemblage body size, temperature and UV‐B irradiation. Annual temporal changes in lightness were examined for a subset of the data. Results Assemblages with large average body sizes were darker in colour than those with small body sizes. Assemblages became lighter in colour with increasing temperature, but darkened again at the highest temperatures when there were high levels of UV‐B. Through time, temperature and body size explained variation in lightness. Both the spatial and temporal models explained c . 50% of the variation in lightness. Main conclusions Our results are consistent with the thermal melanism hypothesis, and demonstrate the importance of considering body size and UV‐B radiation exposure in explaining the colour of insect cuticle. Crucially, this finding is at the assemblage level. Consequently, the relative abundances and identities of ant species that are present in an assemblage can change in accordance with environmental conditions over elevation, latitude and relatively short time spans. These findings suggest that there are important constraints on how ectotherm assemblages may be able to respond to rapidly changing environmental conditions.

Invasive Cane Toads’ Predatory Impact on Dung Beetles is Mediated by Reservoir Type at Artificial Water Points - Benjamin Feit; Tim Dempster; Heloise Gibb; Mike Letnic (Ecosystems, 2015)

Effects of reconstruction of a pre-European vertebrate assemblage on ground-dwelling arachnids in arid Australia - Colin J. Silvey; Matthew W. Hayward; Heloise Gibb (Oecologia, 2015)

Fine‐scale heterogeneity in beetle assemblages under co‐occurring Eucalyptus in the same subgenus - Philip S. Barton; Adrian D. Manning; Heloise Gibb; David B. Lindenmayer; Saul A. Cunningham (Journal of Biogeography, 2010)
Aim Insect biodiversity is often positively associated with habitat heterogeneity. However, this relationship depends on spatial scale, with most studies focused on differences between habitats at large scales with a variety of forest tree species. We examined fine‐scale heterogeneity in ground‐dwelling beetle assemblages under co‐occurring trees in the same subgenus: Eucalyptus melliodora A. Cunn. ex Schauer and E. blakelyi Maiden (Myrtaceae). Location Critically endangered grassy woodland near Canberra, south‐eastern Australia. Methods We used pitfall traps and Tullgren funnels to sample ground‐dwelling beetles from the litter environment under 47 trees, and examined differences in diversity and composition at spatial scales ranging from 100 to 1000 m. Results Beetle assemblages under the two tree species had distinctive differences in diversity and composition. We found that E. melliodora supported a higher richness and abundance of beetles, but had higher compositional similarity among samples. In contrast, E. blakelyi had a lower abundance and species richness of beetles, but more variability in species composition among samples. Main conclusions Our study shows that heterogeneity in litter habitat under co‐occurring and closely related eucalypt species can influence beetle assemblages at spatial scales of just hundreds of metres. The differential contribution to fine‐scale alpha and beta diversity by each eucalypt can be exploited for conservation purposes by ensuring an appropriate mix of the two species in the temperate woodlands where they co‐occur. This would help not only to maximize biodiversity at landscape scales, but also to maintain heterogeneity in species richness, trophic function and biomass at fine spatial scales.

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Insect natural enemies of Ips typographus (L.) (Coleoptera, Scolytinae) in managed and unmanaged stands of mixed lowland forest in Poland - Jacek Hilszczański; Heloise Gibb; Cezary Bystrowski (Journal of Pest Science, 2007)

Effects of low severity burning after clear-cutting on mid-boreal ant communities in the two years after fire - Heloise Gibb; Joakim Hjältén (Journal of Insect Conservation, 2007)

Dominant meat ants affect only their specialist predator in an epigaeic arthropod community - Heloise Gibb (Oecologia, 2003)